Implementasi Metode Iqro’ Al-Mansury dalam Meningkatkan Kemampuan Anak Membaca dan Menghafal Al-Qur’an di PAUD Al-Azhaar Kota Lubuklinggau - Purnama Shalihah, Barratus; -, Rohimin (UIN Fatmawati Sukarno Bengkulu, 2025)
One method in learning to read the Qur'an with the Iqro' method is the method in the Iqro' Al-Mansury book, the method used in the Iqro' Al-Mansury book by Dr. KH Ah Mansur, SE., M.Pd.I, which is a guidebook for reading the Qur'an for children. In this book, the method used is an interactive-integrative method between the talaqi method and games so that it can provide a new nuance in the treasure trove of learning to read the Qur'an. At the Al Azhaar PAUD institution in Lubuklinggau City, in learning to read the Qur'an, the Iqro' Al-Mansury book is used as a method of learning the Qur'an. This study uses a descriptive qualitative research method. The data sources used are primary and secondary data sources using three data collection methods, namely interviews, observation and documentation. The collected data will be analyzed using descriptive analysis. Based on the data analysis, the Al-Azhaar Early Childhood Education (PAUD) in Lubuklinggau City has implemented the Iqro' Al Mansury method to improve children's understanding of reading the Quran. This method has been implemented for the past year. Research shows that children are more enthusiastic about learning using the Iqro' Al Mansury book because it includes talaqi (recitation) and independent methods, as well as a combination of games and songs. This allows them to more quickly understand the hijaiyah letters and read the Quran.